Cognitive linguistics - Croft, William (Cambridge textbooks in linguistics., 2004)
Cognitive Linguistics argues that language is governed by general cognitive principles, rather than by a special-purpose language module. This introductory textbook surveys the field of cognitive linguistics, presenting its theoretical foundations and the arguments supporting it. Clearly organised and accessibly written, it provides a useful introduction to this fast-growing area.